2008
DOI: 10.1111/j.1530-0277.2008.00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Restraint Stress and Ethanol Consumption in Two Mouse Strains

Abstract: Background-This study examined the interaction between restraint stress and ethanol drinking in mice that consume low and high amounts of ethanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 38 publications
2
37
0
Order By: Relevance
“…In agreement with this analysis, it has been shown that while mifepristone has no effect on baseline drinking in mice, it blocks stress-induced increases in drinking caused by daily vehicle injections (O'Callaghan et al, 2005). In conditions where stress is limited, mifepristone has no effect on ethanol intake (Fahlke et al, 1994(Fahlke et al, , 1995(Fahlke et al, , 1996Lowery et al, 2010;Yang et al, 2008).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In agreement with this analysis, it has been shown that while mifepristone has no effect on baseline drinking in mice, it blocks stress-induced increases in drinking caused by daily vehicle injections (O'Callaghan et al, 2005). In conditions where stress is limited, mifepristone has no effect on ethanol intake (Fahlke et al, 1994(Fahlke et al, , 1995(Fahlke et al, , 1996Lowery et al, 2010;Yang et al, 2008).…”
Section: Discussionsupporting
confidence: 63%
“…The literature is somewhat mixed when examining the effects of mifepristone on ethanol consumption as some authors have reported decreases in consumption following drug treatment (Koenig and Olive, 2004;O'Callaghan et al, 2005), while others have reported no change (Fahlke et al, 1994(Fahlke et al, , 1995(Fahlke et al, , 1996Lowery et al, 2010;Yang et al, 2008). Koenig and Olive (2004) demonstrated significant decreases in consumption using a limited-access, two-bottle-choice paradigm; however, it is important to note that the animals were fluid restricted for 23 h a day (O'Callaghan et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…One important feature of AAA models is the definition of biologically meaningful levels of alcohol, either in vitro or in vivo, and their relationship to blood alcohol levels (BAL) in humans. This is an important requirement of the research models of AAA, because BAL can be detected as soon as minimal amounts of alcohol are ingested [85] , however measurable affects of alcohol on physiology and/or behavior is established at 0.08% or above this level, with individual variations depending on the species, metabolic particularities, age, gender and genetic background [86][87][88][89][90][91][92][93][94][95][96][97] . It is also important to identify that AAA models differ by their route of alcohol delivery to achieve alcohol intoxication, some of them being physiological, such as oral administration, while others being non-physiological, when ethanol is administered by parenteral routes.…”
Section: Models Of Aaamentioning
confidence: 99%
“…Among non-human vertebrates commonly involved in alcohol research are primates [90,91,148] , pigs [104,120] , dogs [114,121] , mice [70,72,74,86,89,96,109,118,119,141] , rats [88,94,108,149,150] and rabbits [132] . The rodent AAA models (mice and rats) are used most frequently due to their relatively well-defined genetic background and the availability of diverse genetic traits, including those coding for high or low alcohol consumption [88,89,96,109] .…”
Section: Non-human Aaa Modelsmentioning
confidence: 99%